Iman akan Allah Bapa dalam Pengalaman Hidup Rohani Frater di Seminari Tinggi Giovanni Malang - Antonius Denny Firmanto; Adry Yanto Saputra (Sekolah Tinggi Teologi Berita Hidup, 2023)
As a prospective priest, this understanding is important as a preacher to teach the people. However, before teaching as a subject, a reporter needs to understand and live it well. The focus of this research theme is spiritual life. Spiritual life as a candidate for priest is very important because prospective priests (brothers) are preachers of the faith. The purpose of this research is to explore the extent of understanding and living faith in God the Father. why is the title of God as Father important to be understood by every prospective priest? Why is the living of faith in God the brothers important in the life of formation in the community? The focus of this research is for each class representative of the brothers at the Seminary Giovanni Malang. The brothers are increasingly aware that the title God the Father is not arbitrary, but has meaning and meaning for people who believe in Allah. Each class representative was asked to fill in the prepared questions. The modotology used in this study is to use the interview method. This model analysis uses the same answer classifications from each research subject. Presenting the summary result data and making preliminary conclusions. From the results of questionnaires and supported from books, articles and reflections. From the results of this study, it is found that knowledge about God the Father comes from the stories of the Bible, family and faith educators such as catechists and priests. The understanding of faith is also very influential in our appreciation. Almost all subjects answered the knowledge of God the Father from the Scriptures, some because of parental role models, priests' personal relationships in prayer. Spiritual life is also very influential in living faith. Personal prayer, worship, mass, reflection, meditation and the sacrament of penance are tools for building more personal relationships.